Flows In and Out of Self-Employment - Lawless, Martina; O'Brien, Patrick; Rehill, Luke (The Economic and Social Review, 2024)
The establishment and growth of new businesses are key ingredients for economic growth and job creation across economies. As such, a key objective for policymakers is targeting institutional and policy objectives that encourage entrepreneurship. Importantly, the literature on entrepreneurship distinguishes between types of entrepreneurs and their drivers; namely those motivated by ‘necessity’ or ‘opportunity’. A key differentiating characteristic is how each are correlated with broader economic cycles, i.e. necessity entrepreneurship is more likely to occur as other options for employment diminish rather than expand. To examine this in an Irish context, this research uses employment status information from the Labour Force Survey to examine the characteristics of the self-employed and the extent to which the determinants of becoming self-employed changed against the background of dramatic changes in economic conditions.